2006
DOI: 10.1111/j.1462-2920.2006.01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome analysis of the marine BacteroidetesGramella forsetii’ reveals adaptations to degradation of polymeric organic matter

Abstract: Members of the Bacteroidetes, formerly known as the Cytophaga-Flavobacteria-Bacteroides (CFB) phylum, are among the major taxa of marine heterotrophic bacterioplankton frequently found on macroscopic organic matter particles (marine snow). In addition, they have been shown to also represent a significant part of free-living microbial assemblages in nutrient-rich microenvironments. Their abundance and distribution pattern in combination with enzymatic activity studies has led to the notion that organisms of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
270
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(290 citation statements)
references
References 62 publications
12
270
0
2
Order By: Relevance
“…This agrees with previous observations from field (Crump et al ., 2003; Roiha et al ., 2011) and laboratory experiments (Logue et al ., 2016) showing that rapid shifts in community composition take place upon soil organic matter input. The loss and prevalence of the taxa determined in our study may be explained by their different functional adaptability, including differences in resource affinities (Cottrell & Kirchman, 2000; Salcher et al ., 2011; Heinrich et al ., 2013), physiological characteristics (Hahn & Pöckl, 2005; Šimek et al ., 2006) and genetic composition (Bauer et al ., 2006; Gómez‐Pereira et al ., 2012; Teeling et al ., 2012; Tveit et al ., 2013). Further, changes in lake bacterial community composition have been attributed not only to the differential response of individual bacterial taxa to DOM inputs, but also to the introduction of soil bacteria with allochthonous sources or to incubation effects (Crump et al ., 2003; Logue et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with previous observations from field (Crump et al ., 2003; Roiha et al ., 2011) and laboratory experiments (Logue et al ., 2016) showing that rapid shifts in community composition take place upon soil organic matter input. The loss and prevalence of the taxa determined in our study may be explained by their different functional adaptability, including differences in resource affinities (Cottrell & Kirchman, 2000; Salcher et al ., 2011; Heinrich et al ., 2013), physiological characteristics (Hahn & Pöckl, 2005; Šimek et al ., 2006) and genetic composition (Bauer et al ., 2006; Gómez‐Pereira et al ., 2012; Teeling et al ., 2012; Tveit et al ., 2013). Further, changes in lake bacterial community composition have been attributed not only to the differential response of individual bacterial taxa to DOM inputs, but also to the introduction of soil bacteria with allochthonous sources or to incubation effects (Crump et al ., 2003; Logue et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported high relative abundance of Bacteroidetes or Planctomycetes following algal blooms [56][57][58][59][60]. Both phyla are known to be present and attached to aggregates, and they have various extracellular enzymes that can degrade complex organic molecules and give a competitive advantage with regards to other microbial groups [61][62][63]. Presence of a high percentage of these two phyla in different seasons might be due to the competition between these two phyla for organic matter or dominance of different phytoplankton species in two seasons, as mainly a higher dominance of diatoms was observed in the DS and Cyanobacteria were more dominant in the RS ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity and novelty of the Bacteroidetes Phylum, specially the Flavobacteria family, are also underscored by the fact that many microbes in this family have been phylogenetically reclassified from different initial assignments (Jooste and Hugo 1999;Yoon et al 2012). (b) Degradative enzymes: Many DFI organisms are heterotrophs, encoding genes for degradative enzymes that allow them to survive on diverse high molecular weight compounds; such enzymes include protease, sulfatase, pectinase, chitinase, and α-amylases (Jooste and Hugo 1999;Abt et al 2011;Bauer et al 2006;Kirchman 2002;Klippel et al 2011). Some in fact derive their names from the ability to degrade and scavenge.…”
Section: Dfi Genes Occur In Select Microorganisms Onlymentioning
confidence: 99%